2020
DOI: 10.1136/bjophthalmol-2020-316004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of intermediate age-related macular degeneration phenotypes for geographic atrophy progression

Abstract: BackgroundTo characterise early stages of geographic atrophy (GA) development in age-related macular degeneration (AMD) and to determine the prognostic value of structural precursor lesions in eyes with intermediate (i) AMD on the subsequent GA progression.MethodsStructural precursor lesions for atrophic areas (lesion size at least 0.5 mm² in fundus autofluorescence images) were retrospectively identified based on multimodal imaging and evaluated for association with the subsequent GA enlargement rates (square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The term macular degeneration indicates a degenerative process of the retina at the level of the fovea, which impairs visual acuity, and it is characterized at the pathological level by the presence of drusen between the retinal pigment epithelium (RPE) and the Bruch’s membrane, as defined in the authoritative review papers by de Jong and Jager et al [ 3 , 4 ]. Similar to drusen, “pseudo-drusen” or “subretinal drusenoid deposits” occurring between the RPE and the boundary between the inner and outer segments of the photoreceptors are associated with an increased risk of developing advanced AMD [ 10 , 11 , 12 , 13 ]. In AMD, extra-macular areas may be involved early on, while in later stages, a widespread degeneration often appears involving both macular and extra-macular regions, which is defined as “geographic atrophy” (GA) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The term macular degeneration indicates a degenerative process of the retina at the level of the fovea, which impairs visual acuity, and it is characterized at the pathological level by the presence of drusen between the retinal pigment epithelium (RPE) and the Bruch’s membrane, as defined in the authoritative review papers by de Jong and Jager et al [ 3 , 4 ]. Similar to drusen, “pseudo-drusen” or “subretinal drusenoid deposits” occurring between the RPE and the boundary between the inner and outer segments of the photoreceptors are associated with an increased risk of developing advanced AMD [ 10 , 11 , 12 , 13 ]. In AMD, extra-macular areas may be involved early on, while in later stages, a widespread degeneration often appears involving both macular and extra-macular regions, which is defined as “geographic atrophy” (GA) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future investigations could include GA subgroup analysis (such as SDD presence/absence) and the effect on GA growth. 32 , 33 Extensions could include further study of the square root transformation applied to GA subgroups using the best three regression models in the comparison (linear, logarithmic, and Q2 models).…”
Section: Discussionmentioning
confidence: 99%
“…The results from the Age-Related Eye Disease Study (AREDS) showed a strong association between drusen and the development of MA. Drusen were found in 100% of eyes at sites where MA later developed [52, 53], and the presence of multiple large drusen increases the probability of developing MA (15-year odds ratio [OR] 14.5, 95% confidence interval 5.9–35.7; 10-year rate of 26% in patients aged 75–80 years) [9, 54]. Likewise, drusen-associated materials are linked to a higher risk of developing MA.…”
Section: Potential Risk Factors For the Development Of Mamentioning
confidence: 99%
“…Development of atrophy often follows collapse of PEDs [54, 80, 81]. There are 3 major types of PEDs that occur in AMD: serous, drusenoid, and PEDs secondary to subretinal neovascularization [82].…”
Section: Potential Risk Factors For the Development Of Mamentioning
confidence: 99%